Figur yang Hilang, Keyakinan yang Terganggu: Tinjauan Literatur tentang Kepercayaan Diri Anak Fatherless: Penelitian - Marssel M. Sengkey; Nova Lisye Sinaulan; Queen Maharani Kartika Kalalo; Varel Eldad Onemarch Mamuaja; Wenly Napoleon Ontolay; Yesi Padoma (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study investigates the effects of the fatherless phenomenon on college students' self-confidence by conducting a thorough literature review. The presence of a father within the family setting is crucial for a child's identity formation, personal growth, and psychological well-being. Nevertheless, the issue of father absence, often referred to as fatherlessness, remains a pressing concern in Indonesia. Data from 2021 indicates that approximately 20.9% of Indonesian children are raised without a father figure. This absence significantly affects the development of self-confidence, particularly among those transitioning into early adulthood. This study adopts a qualitative methodology through a literature review, drawing upon credible scientific publications from the past five to ten years. The findings suggest that fatherlessness has a tangible influence on children's levels of self-confidence and their overall psychosocial adjustment. Identified effects include challenges in decision-making, increased social anxiety, identity confusion, academic decline, and difficulty forming meaningful social relationships. Children growing up without paternal involvement often exhibit low self-esteem, social withdrawal, and a reduced capacity to trust others.